The Role of Corals on Tsunami Dynamics in an Island Setting: A Case Study of Tutuila Island - DILMEN, DERYA Itir (My University, 2016)
On September 29, 2009 at 17:48 UTC, an Mw = 8.1 earthquake in the Tonga Trench generated a tsunami that caused heavy damage across Samoa, American Samoa, and Tonga. One of the worst localities hit was the volcanic island of Tutuila in American Samoa. Tutuila Island, located 250 km from earthquake epicenter, experienced tsunami inundation and strong currents on the north and east coasts, causing 34 fatalities and widespread structural and ecological damage. The surrounding coral reefs of the island also suffered heavy damage. This damage was formally evaluated based on detailed surveys before and immediately after the tsunami, which provides a unique opportunity to evaluate the role of coral reefs on tsunami dynamics. In the first part of this research, estimates of tsunami dynamics are obtained with the MOST numerical tsunami model (Titov and Synolakis, 1997), which is currently the operational tsunami forecast tool used by the US National Oceanic and Atmospheric Administration (NOAA). The earthquake source function was constrained using real-time deep-ocean tsunami data from three DART® (Deep-ocean Assessment and Reporting for Tsunamis) systems in the far field, and by tide-gauge observations in the near field. We compare the numerically estimated run-up with observations to evaluate the simulation skill of MOST. We present an overall synthesis of tide-gage data, survey results of the run up, inundation measurements, and the datasets of coral damage around the island, in order to evaluate the overall accuracy of MOST run-up prediction for Tutuila and the model’s performance of simulating in the locations covered with corals during the tsunami event. Our primary findings are 1) there is a tendency for MOST to underestimate run-up on Tutuila and 2) the locations where the model underestimates run-up tend to have experienced heavy or very heavy coral damage, whereas well-estimated run-up locations characteristically experienced low or very low damage. This brought us to the conclusion regarding how coral reefs affect tsunami dynamics through their influence on bathymetry and dissipation. Second, we focus on numerical simulations of this event to evaluate: 1) how roughness variations affect tsunami run-up and if different values of Manning’s roughness, n, improve the simulated run-up compared to observations; and 2) how depth variations in coral reef bathymetry control run-up and inundation on the coastlines they shield. We find as a result of the simulations that no single value of n provides the best match to observations, and we find large bay-to-bay variations in the impact of varying n. The results suggest that there are aspects of tsunami wave dissipation that are not captured by the drag formulation in the MOST model. The primary impact of removing coral bathymetry is to reduce run-up, from which we conclude that at least in this setting the bathymetric impact of coral reefs is to increase run-up and inundation. We conclude that future studies should focus on two key issues for further research: 1) the representation of the turbulent dissipation in terms of the governing equations and their coefficients and 2) detailed numerical experiments on all aspects of reef settings such as reef widths, reef types and coastal geometry on the scale of individual bays.
Thesis (Ph.D.)--University of Washington, 2016-07
Keywords: Coral; Island; Numerical; Reef; Samoa; Tsunami; Ocean engineering; Civil engineering; Geophysics; earth and space sciences